“EMERGENCY EXIT” SEBAGAI SARANA PENYELAMATAN PENGHUNI PADA BANGUNAN-BANGUNAN SKALA BESAR - Sumardjito Sumardjito (Inersia : Jurnal Teknik Sipil dan Arsitektur, 2010)
Emergency exit facilities as an equipment to evacuate people/occupants fromemergency situation at a building, particularly at a big scale building; vertical scale (highrise building) and horizontal scale (large building). Fixing and type of emergency exit facilities are very variative depends on the building function, highrise and mega building, and the condition of the building itself against emergency situation. Type of emergency situation of the building are very variative, classified in 3 categories : emergency situation caused of nature (earthquake, flood, storm), emergency condition caused of man made( fire, terrorism, etc), and emergency condition caused of technical error (construction collapse due to aging). The different of conditions and types of this emergency condition has the similar effects ; made some victims, but need a differentemergency exit facilities anticipation should be established to evacuate the occupants.Therefore, emergency exit facilities, particularly at a mega building more over with it function as a commercial building which was assumptioned with high occupantions should be really accurately planned and designed. Accuracy in planned and designed should be attention in : building function, classification and categorization of risk level, number of storeys and building total floors and space.Keyword : emergency exit, emergency situation, safety